Impact of leverage, firm size, and audit committees on financial reporting quality: Sri-Kehati - Saraswati, RR. Sri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2024)
Financial statements are an important tool for providing information about a company’s financial management, which supports stakeholders in making informed decisions. To achieve this goal, financial statements must comply with accounting standards and exhibit attributes such as accuracy, comparability, and transparency. This study investigates the impact of leverage, firm size, and audit committee characteristics—including the number of members, frequency of meetings, and financial expertise—on the financial reporting quality of non-financial public companies listed in the SRI-KEHATI Index from 2016 to 2023. Using purposive sampling, this study analyses 72 observation datas from nine companies over eight years, using panel data regression analysis through EViews 12. The results show that while leverage, firm size, and audit committee membership do not significantly affect financial reporting quality, the frequency of audit committee meetings and the number of financial experts on the committee negatively affect financial reporting quality. These findings underscore the need for careful consideration of audit committee practices to improve financial reporting quality.